DETERMINAN INTENSITAS TRANSFER PRICING PADA PERUSAHAAN NON-KEUANGAN AFILIASI - Ilham Teguh Setiawan; Yulis Sarah Rizkya (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2020)
The purpose of this research is aimed the determinants intensity of transfer pricing practices by non-financial multinational companies listed on the IDX during the 2014-2017 period. This research used secondary data analyisis of financial statement of multinational companies. By using purposive sampling method, the total amount of samples obtained in this research was 60 companies over four periods (2014-2017). This research used multiple linear regression analysis, with the classic assumption test first being done. The results of the regression test in this study are from taxes, profitability, and firm size have a negative and not significant influence toward the firm decision for transfer pricing, while intangible assets have a positive and significant effect toward the firm decision for transfer pricing. Related to these four independent variables, intangible assets are the determinant factors of transfer pricing.